Evaluación de control del inventario en el Comercial Don Saúl de la ciudad de Babahoyo, en el período 2022 - Muñoz Sañay, Ámbar Anthonella (2023)
This study focuses on the Evaluation of Internal Control in the Inventory Management of "Don Saúl" Commercial during the year 2022, with the general objective of determining its level of reliability according to the COSO model. The problem statement highlights deficiencies in "Don Saúl's" inventory control, including issues related to expired products, incorrect entry of inventory, defective products, and unauthorized consumption of goods, all of which affect its efficiency and profitability. The justification lies in the need to optimize financial resources, comply with accounting regulations, improve corporate image, enhance operational efficiency, and contribute to accounting knowledge through this study. The methodology involved a detailed interview with the manager of "Don Saúl" to gather relevant information about internal inventory control. A matrix based on the COSO model was used to assess compliance levels in different control categories, such as control environment, risk assessment, control activities, information and communication, and monitoring. The conclusions highlight the identification of deficiencies in the control of expired products and the finding that some companies only recognize 50% of expired products, resulting in losses. The importance of having documented policies and procedures is emphasized, as well as the need for regular physical inventory counts to ensure the accuracy of records. Furthermore, increased internal communication and training for inventory management staff are recommended